Analisis Pengembangan Bisnis UMKM Songket XYZ Palembang melalui Pendekatan Business Model Canvas (BMC) untuk Peningkatan Strategi Pemasaran - Pelixka Pelixka; M Fikri Mulyadi; Nadya Zulfa Widodo; Muhammad Hasyim; Nidya Wisudawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
MSMEs play a crucial role in navigating the dynamics of competition in the digital era, including Songket XYZ Palembang, which produces traditional woven fabrics. This study aims to analyze and design a more adaptive business model using the Business Model Canvas (BMC) (BMC) approach to improve the effectiveness of marketing strategies. The research methods used were observation, interviews, and analysis of ongoing business processes. The results showed that all elements of the BMC were strengthened, such as expanding customer segmentation, sharpening value propositions, optimizing digital marketing channels, and improving the quality of customer relationships. Furthermore, key resources, core activities, and strategic partners were structured more comprehensively to support business competitiveness. The improved business model also resulted in a more diverse cost structure and revenue streams. Overall, the implementation of the BMC provides a more effective strategic direction for the development of the Songket XYZ MSME.